Ensuring the right to defense during the notification of suspicion in state treason cases - Байдик , Олександр Анатолійович (Київський національний університет імені Тараса Шевченка, ТОВ «Правова Єдність», 2024)
The article provides a comprehensive analysis of the procedural role of the defense counsel during the notification of suspicion in crimes provided for in Article 111 of the Criminal Code of Ukraine, taking into account the peculiarities of the current state of national legislation, the practice of its application, and international standards of the right to a fair trial. The purpose of the article is to define the theoretical, legal, and practical foundations of the defense counsel’s participation in the procedure of notifying a person of suspicion, to identify the main problems of exercising the right to defense in state treason cases, and to develop proposals for improving the criminal procedural legislation of Ukraine in order to ensure the genuine, rather than formal, participation of the defense counsel at this stage of pre-trial investigation. The study reveals the essence of the defense function as an integral element of the mechanism for ensuring the rule of law, the presumption of innocence, and the guarantees of a fair trial. It is determined that the notification of suspicion is not only a procedural act aimed at informing a person of the existence of sufficient data for a reasonable suspicion but also a legal fact that changes the person’s procedural status and creates conditions for the exercise of the right to effective defense. The article generalizes the provisions of criminal procedural legislation and judicial practice concerning the ensuring of the right to defense at the stage of notifying a person of suspicion. The main shortcomings of law enforcement practice are identified, including the absence of a legally established mandatory participation of a defense counsel in this procedure, the restriction of defense counsels’ access to pre-trial investigation materials containing classified information, and the violation of the principle of confidentiality of legal assistance. It is proved that effective participation of the defense counsel at the initial stage of criminal proceedings is a prerequisite for the observance of the principles of adversarial proceedings, equality of arms, and fairness of the judicial process. Based on the generalization of scientific doctrine and Supreme Court practice, the article proposes directions for improving the criminal procedural legislation, including the introduction of mandatory participation of the defense counsel during notification of suspicion in proceedings concerning crimes against the foundations of national security, the establishment of judicial control over the reasonableness of suspicion, the development of methodological recommendations for pre-trial investigation bodies, and the implementation of audio or video recording of the moment of notification. It is concluded that strengthening the role of the defense counsel in this procedural action is a necessary condition for increasing the effectiveness of criminal proceedings, ensuring the protection of human rights, and affirming the rule of law in Ukraine.

Стаття присвячена всебічному аналізу процесуальної ролі захисника під час повідомлення про підозру у злочинах, передбачених статтею 111 Кримінального кодексу України, з урахуванням особливостей сучасного стану національного законодавства, практики його застосування та міжнародних стандартів права на справедливий суд. Метою статті є визначення теоретико-правових і практичних засад участі захисника у процедурі повідомлення про підозру, виявлення основних проблем реалізації права на захист у справах про державну зраду та розроблення пропозицій щодо вдосконалення кримінального процесуального законодавства України з метою забезпечення реальної, а не формальної участі адвоката на цій стадії досудового розслідування. У дослідженні розкрито сутність функції захисту як невід’ємного елемента механізму забезпечення верховенства права, презумпції невинуватості та гарантій справедливого судового розгляду. З’ясовано, що повідомлення про підозру є не лише процесуальною дією, спрямованою на інформування особи про наявність достатніх даних для обґрунтованої підозри, а й юридичним фактом, який змінює її правовий статус і створює умови для реалізації права на ефективний захист. У статті здійснено узагальнення положень кримінального процесуального законодавства та судової практики щодо забезпечення права на захист на етапі повідомлення про підозру. Визначено основні недоліки правозастосування, серед яких відсутність законодавчо закріпленої обов’язкової участі захисника у цій процедурі, обмеження доступу адвокатів до матеріалів досудового розслідування, що містять відомості з обмеженим доступом, та порушення принципу конфіденційності адвокатської діяльності. У статті доведено, що ефективна участь захисника на початковому етапі кримінального провадження є передумовою дотримання принципів змагальності, рівності сторін і справедливості судового розгляду. На основі узагальнення положень наукової доктрини та практики Верховного Суду запропоновано напрями вдосконалення кримінального процесуального законодавства, серед яких – закріплення обов’язкової участі захисника під час повідомлення про підозру у провадженнях щодо злочинів проти основ національної безпеки, запровадження судового контролю за обґрунтованістю підозри, розроблення методичних рекомендацій для органів досудового розслідування та забезпечення аудіочи відеофіксації моменту повідомлення про підозру. Зроблено висновок, що посилення ролі захисника у цій процесуальній дії є необхідною умовою підвищення ефективності кримінального провадження, дотримання прав людини та утвердження верховенства права в Україні.
Забезпечення права на захист при повідомленні про підозру у державній зраді
Keywords: defense counsel; right to defense; notification of suspicion; state treason; criminal proceedings; procedural guarantees; judicial control; rule of law; presumption of innocence; fair trial; захисник; право на захист; повідомлення про підозру; державна зрада; кримінальне провадження; процесуальні гарантії; судовий контроль; верховенство права; презумпція невинуватості; справедливий суд